Measuring the effect of thrombosis, thrombus maturation and thrombolysis on clot mechanical properties in an in-vitro model. (2nd December 2021) - Dwivedi, Anushree; Glynn, Aoife; Johnson, Sarah; Duffy, Sharon; Fereidoonnezhad, Behrooz; McGarry, Patrick; Gilvarry, Michael; McCarthy, Ray; ,
Abstract: Changes in acute ischemic stroke thrombi structure and composition may result in significant differences in treatment responsiveness. Ischemic stroke patients are often treated with a thrombolytic agent to dissolve thrombi, however these patients may subsequently undergo mechanical thrombectomy to remove the occlusive clot. We set out to determine if rt-PA thrombolysis treatment of blood clots changes their mechanical properties, which in turn may impact mechanical thrombectomy. Using a design-of-experiment approach, ovine clot analogues were prepared with varying composition and further exposed to different levels of compaction force to simulate the effect of arterial blood pressure. Finally, clots were treated with three r-tPA doses for different durations. Clot mass and mechanical behaviour was analysed to assess changes due to (i) Platelet driven contraction (ii) Compaction force and (iii) Thrombolysis. Clots that were exposed to r-tPA for longer duration showed significant reduction in clot mass (p < 0.001). Exposure time to r-tPA (p < 0.001) was shown to be an independent predictor of lower clot stiffness. A decrease in energy dissipation ratio during mechanical compression was associated with longer exposure time in r-tPA (p = 0.001) and a higher platelet concentration ratio (p = 0.018). The dose of r-tPA was not a significant factor in reducing clot mass or changing mechanical properties of the clots. Fibrinolysis reduces clot stiffness which may explain increased distal clot migration observed in patients treated with r-tPA and should be considered as a potential clot modification factor before mechanical thrombectomy.